Erdheim-Chester Disease Associated with Marginal Zone Lymphoma and Monoclonal Proteinemia - Peter G. Pavlidakey; Alok Mohanty; Lisa J. Kohler; Howard J. Meyerson (Case Reports in Hematology)
Erdheim-Chester disease (ECD) is a rare non-Langerhans cell histiocytosis. We report a fatal case of ECD with extensive cardiac involvement associated with a marginal zone lymphoma and monoclonal proteinemia in a young man. This is the first reported association of ECD with a monoclonal gammopathy or a lymphoma.